The signaling effect of management response in engaging customers: A study of the hotel industry. (October 2017) - Li, Chunyu; Cui, Geng; Peng, Ling
Abstract: Hotels today actively respond to online reviews given their tremendous influence on travelers' decisions. Yet, the questions of how to respond to online reviews continue to baffle hotel managers. By focusing on prospective travelers, we propose the effective management response signals hotels' care for customers and quality of service. Particularly, we postulate the frequency, speed and length of response influence the effectiveness of signaling in reducing information asymmetry. Based on the large-scale field data from TripAdvisor, this study demonstrates that the frequency and speed of response significantly enhance travelers' engagement as indicated by more reviews, higher average valence, more votes for helpfulness, and higher popularity ranking. Furthermore, the frequent and speedy response is more effective for budget (vs. premium) hotels. Thus, management response to online reviews serves as a critical channel of communication to engage customers. Highlights: Management response is a continuous, dynamic and reciprocal communication process. Response attributes shapes the effectiveness of management response by involving different signaling cost. The frequency and speed of response show significant signaling effect and enhance customer engagement on social media. Signaling effect of management response is more pronounced for budget hotels than for premium hotels.